2013
DOI: 10.1007/s11432-013-4835-4
|View full text |Cite
|
Sign up to set email alerts
|

Beautiful, usable, and popular: good experience of interactive products for Chinese users

Abstract: User experience (UX) is essential for creating successful interactive products. However, whether the evaluation of user experience is universal across different cultures is questionable. In the past decades, a large number of researches have demonstrated consistently that different cultures play an important role in influencing people's perception and cognition of the world. These cultural differences can also influence people's aesthetic judgments and experience of products. The main goals of our research wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, additional explanations for the influence of these factors on overall experience in using WRs should be found. A possible explanation is social influence such as conformity [ 62 ], but this should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional explanations for the influence of these factors on overall experience in using WRs should be found. A possible explanation is social influence such as conformity [ 62 ], but this should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The interfaces matching cultural preferences can increase the user experience, such as usability and aesthetics. Liu et al [52] explored how Chinese users evaluated the user experience of cellphones. The results demonstrated that three critical factors for users' experience of cellphones interfaces, namely Hedonic Quality, Pragmatic Quality, and Conformity instead of the four factors in Western culture.…”
Section: User Experience: Structure Measurement and Cultural Influencesmentioning
confidence: 99%
“…Second, an eye-tracking experiment was performed to collect viewers' eye movement data. Third, selected paintings were rated on four aesthetic dimensions based on AttrakDiff [4][5][6], reported in the Experiments section. We next review related work, followed by our conclusions.…”
mentioning
confidence: 99%